Fabrication of p-type (MCCO) thin film using DC magnetron sputtering as a preparator for thermoelectric module - Irawan, Elysa Nensy; Aslami, Fahrur; Janotama, Muhammad Matthew; Putra, Aldo Mahendra; Muntini, Melania Suweni; Thaowankaew, Somporn; Namhongsa, Wanatchaporn; Vora-Ud, Athorn; Singsoog, Kunchit; Seetawan, Tosawat (Journal of Physics: Theories and Applications, 2023)
Based on existing research, thermoelectric efficiency can be improved through material selection. In this study, the material used is CaCO₃ doped with Mn and Co₂O₃ to form CaCo3.5Mn0.5O9 material as a p-type thermoelectric material. The substrate used is glass. The stages in this research are material synthesis, sputtering process using DC Magnetron Sputtering machine to form thin films, and testing. The synthesis process includes grinding, calcination, and sintering. Grinding is done using a Ball Mill machine with a rotation speed of 250 rpm for 5 hours. Furthermore, the calcination step was carried out by heating the sample into a furnace at a temperature of 800°C for 10 hours. Then the sintering process was carried out at a temperature of 850°C for 12 hours. After the synthesis process is complete, enter the sputtering process using a DC Magnetron Sputtering machine for approximately 10 minutes. The gas used in this research is Argon (Ar). After the sputtering process was carried out, several tests appeared, such as the XRD test to determine the type of crystal, the ZEM-3 test to determine the Seebeck coefficient and resistivity, the thickness of the thin film formed, and the power factor test to determine the maximum voltage and power generated by the module formed. Several power factor test results were obtained, consisting of 107 μW/mK² at 100°C, 108 μW/mK² at 200°C, and 332 μW/mK² at 300°C and a thickness of 90.34 nm.